2012
DOI: 10.1186/1744-8069-8-60
|View full text |Cite
|
Sign up to set email alerts
|

Salvinorin A Reduces Mechanical Allodynia and Spinal Neuronal Hyperexcitability Induced by Peripheral Formalin Injection

Abstract: BackgroundSalvinorin A (SA), the main active component of Salvia Divinorum, is a non-nitrogenous kappa opioid receptor (KOR) agonist. It has been shown to reduce acute pain and to exert potent antinflammatory effects. This study assesses the effects and the mode of action of SA on formalin-induced persistent pain in mice. Specifically, the SA effects on long-term behavioural dysfuctions and changes in neuronal activity occurring at spinal level, after single peripheral formalin injection, have been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 57 publications
2
48
0
1
Order By: Relevance
“…While its hallucinogenic properties (Valdés et al, 1983) and short duration of action (Butelman et al, 2009; Prisinzano, 2005; Ranganathan et al, 2012; Teksin et al, 2009) limit its clinical usefulness, SalA has proven preclinical analgesic and anti-inflammatory properties (Aviello et al, 2011; Fichna et al, 2012; Guida et al, 2012; John et al, 2006; McCurdy et al, 2006; Rossi et al, 2016). As a KOPr agonist, SalA is structurally unique and structure–activity studies have shown that the C-2 position of SalA is important for binding to KOPr and metabolic stability (Chavkin et al, 2004; Prisinzano, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While its hallucinogenic properties (Valdés et al, 1983) and short duration of action (Butelman et al, 2009; Prisinzano, 2005; Ranganathan et al, 2012; Teksin et al, 2009) limit its clinical usefulness, SalA has proven preclinical analgesic and anti-inflammatory properties (Aviello et al, 2011; Fichna et al, 2012; Guida et al, 2012; John et al, 2006; McCurdy et al, 2006; Rossi et al, 2016). As a KOPr agonist, SalA is structurally unique and structure–activity studies have shown that the C-2 position of SalA is important for binding to KOPr and metabolic stability (Chavkin et al, 2004; Prisinzano, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Salvinorin A (SalA) is a potent, selective KOPr agonist isolated from the plant Salvia divinorum (Chavkin et al, 2004; Roth et al, 2002). In mice, SalA has anti-nociceptive effects in the tail-withdrawal, hot-plate (McCurdy et al, 2006), abdominal constriction and formalin footpad models (Guida et al, 2012; McCurdy et al, 2006). Whilst SalA has reduced side-effects compared to traditional KOPr agonists, the short duration of action limits its usefulness (Butelman et al, 2009; Prisinzano, 2005; Ranganathan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo electrophysiology was performed as previously reported (Gatta et al, ; Guida et al, ). On the day of the electrophysiological recording experiments, mice were initially anesthetized with sodium pentobarbital (50 mg/kg, intraperitoneally).…”
Section: Methodsmentioning
confidence: 99%
“…S. divinorum is actually primarily used by adolescent and young adults for its hallucinogenic properties with a prevalence of use ranging, for example, from 1.3% among adults in the USA to 11% of attendees to rave musical events in Italy (Mahendran et al, 2016). The main active ingredient of the plant is the neoclerodane diterpenoid Salvinorin A. Pharmacodynamic studies have shown that Salvinorin A is a potent and selective kappa opioid receptor agonist (Roth et al, 2002; Chavkin et al, 2004), may exert CB1-like effects, without being able to activate such receptors (Braida et al, 2007; Capasso et al, 2008; Fichna et al, 2012; Guida et al, 2012). In addition Salvinorin A has demonstrated to exert anti-inflammatory actions (Aviello et al, 2011; Rossi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%